(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
This paper presents the main results from a set of guidelines on the physico-mathematical modelling of laser surface-treatment of wear-resistant implants for human joint replacements. These guidelines contain synthesized and documented procedure, theoretical and practical recommendations, which are provided by researchers in the Nanomaterials Laboratory under the Institute of Fundamental Science and Innovative Technologies, Liepaja University. The present paper does not attempt to cover all aspects of physical and mathematical modelling, but draws together many key aspects concerning theoretical and practical difficulties, in the overcoming of what researchers of the Nanomaterials Laboratory, in particular, the authors of the present paper, have sufficient skills.